Digital timer switch / Zainorshafiq S.M Salim & Mohamad Rasul Izuddin Wahidudden - S.M Salim, Zainorshafiq; Wahidudden, Mohamad Rasul Izuddin (2015)
We planned to use knowledge about technology to develop a simple extension to advance socket extension. For our research, without this project, society always keep wasted electricity usage and cannot use it wisely. This project we names as Digital Timer Switch. This project functioning just like other simple sockets, but this switch can ON and OFF automatically depend on the user. User can set the socket depend how long they want and automatically OFF without user do not have to close it manually. We develop this socket to make it more users friendly. Users can save money from pay expensive electric bill because this socket can control electricity usage. Beside, before this system designed, research about the same project has been done. Knowledge from previous project giving us an idea to improve our project to make it updated to other project.